Akulturasi Budaya Mahasiswa Thailand Dalam Berkomunikasi Pada Proses Perkuliahan Di Banda Aceh - Irza Aska Amalia; Abdul Rani Usman; Azman Sulaiman (Kalam: Jurnal Agama dan Sosial Humaniora, 2026)
This study aims to analyze the process of cultural acculturation of Thai students in communication during the learning process in Banda Aceh, as well as to identify the challenges they encounter. This research employs a qualitative approach with a descriptive phenomenological design. Data were collected through in-depth interviews, observation, and documentation involving Thai students studying at several universities in Banda Aceh. The findings reveal that Thai students experience a gradual process of communication acculturation, particularly in adapting to differences in language, intonation, and communication styles. In the early stages, language barriers and differences in spea king styles lead to difficulties in both academic and social interactions. However, through continuous interaction with local students and the academic environment, their communication skills improve, enabling them to adapt to local communication patterns. This study also identifies several major challenges, including language differences, variations in intonation and speaking styles, limited understanding of terms, and differences in learning systems. Based on Berry’s acculturation theory, the dominant acculturation strategy is integration, where students maintain their original culture while adapting to the local culture. Therefore, communication acculturation plays a crucial role in supporting the academic and social adaptation of Thai students in Banda Aceh.